Optimal. Leaf size=26 \[ \frac {e^{e^x}}{\left (8+e^{x^2}-x\right ) (4-\log (3))} \]
________________________________________________________________________________________
Rubi [A] time = 0.70, antiderivative size = 47, normalized size of antiderivative = 1.81, number of steps used = 3, number of rules used = 3, integrand size = 84, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.036, Rules used = {6688, 12, 2288} \begin {gather*} \frac {e^{e^x-x} \left (e^{x^2+x}+e^x (8-x)\right )}{\left (e^{x^2}-x+8\right )^2 (4-\log (3))} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 2288
Rule 6688
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{e^x} \left (1+e^{x+x^2}-e^x (-8+x)-2 e^{x^2} x\right )}{\left (8+e^{x^2}-x\right )^2 (4-\log (3))} \, dx\\ &=\frac {\int \frac {e^{e^x} \left (1+e^{x+x^2}-e^x (-8+x)-2 e^{x^2} x\right )}{\left (8+e^{x^2}-x\right )^2} \, dx}{4-\log (3)}\\ &=\frac {e^{e^x-x} \left (e^{x+x^2}+e^x (8-x)\right )}{\left (8+e^{x^2}-x\right )^2 (4-\log (3))}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.13, size = 25, normalized size = 0.96 \begin {gather*} -\frac {e^{e^x}}{\left (8+e^{x^2}-x\right ) (-4+\log (3))} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.59, size = 28, normalized size = 1.08 \begin {gather*} -\frac {e^{\left (e^{x}\right )}}{{\left (\log \relax (3) - 4\right )} e^{\left (x^{2}\right )} - {\left (x - 8\right )} \log \relax (3) + 4 \, x - 32} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.21, size = 145, normalized size = 5.58 \begin {gather*} \frac {2 \, x^{2} e^{\left (x + e^{x}\right )} - 16 \, x e^{\left (x + e^{x}\right )} - e^{\left (x + e^{x}\right )}}{2 \, x^{3} e^{x} \log \relax (3) - 8 \, x^{3} e^{x} - 2 \, x^{2} e^{\left (x^{2} + x\right )} \log \relax (3) - 32 \, x^{2} e^{x} \log \relax (3) + 8 \, x^{2} e^{\left (x^{2} + x\right )} + 128 \, x^{2} e^{x} + 16 \, x e^{\left (x^{2} + x\right )} \log \relax (3) + 127 \, x e^{x} \log \relax (3) - 64 \, x e^{\left (x^{2} + x\right )} - 508 \, x e^{x} + e^{\left (x^{2} + x\right )} \log \relax (3) + 8 \, e^{x} \log \relax (3) - 4 \, e^{\left (x^{2} + x\right )} - 32 \, e^{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [F] time = 0.03, size = 0, normalized size = 0.00 \[\int \frac {\left (\left (2 x -{\mathrm e}^{x}\right ) {\mathrm e}^{x^{2}}+\left (-8+x \right ) {\mathrm e}^{x}-1\right ) {\mathrm e}^{{\mathrm e}^{x}}}{\left (-4+\ln \relax (3)\right ) {\mathrm e}^{2 x^{2}}+\left (\left (16-2 x \right ) \ln \relax (3)+8 x -64\right ) {\mathrm e}^{x^{2}}+\left (x^{2}-16 x +64\right ) \ln \relax (3)-4 x^{2}+64 x -256}\, dx\]
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.52, size = 28, normalized size = 1.08 \begin {gather*} \frac {e^{\left (e^{x}\right )}}{x {\left (\log \relax (3) - 4\right )} - {\left (\log \relax (3) - 4\right )} e^{\left (x^{2}\right )} - 8 \, \log \relax (3) + 32} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 3.60, size = 22, normalized size = 0.85 \begin {gather*} -\frac {{\mathrm {e}}^{{\mathrm {e}}^x}}{\left (\ln \relax (3)-4\right )\,\left ({\mathrm {e}}^{x^2}-x+8\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.26, size = 34, normalized size = 1.31 \begin {gather*} \frac {e^{e^{x}}}{- 4 x + x \log {\relax (3 )} - e^{x^{2}} \log {\relax (3 )} + 4 e^{x^{2}} - 8 \log {\relax (3 )} + 32} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________